Penerapan Coaching Pada Guru PAUD dalam Meningkatkan Efikasi Diri dalam Mengajar Berdasarkan Kurikulum Merdeka - Damayanti, Eka; Patiung, Dahlia; Jumrah, Nurwahdhani Mawahda (Early Childhood Islamic Education, 2024)
Implementing the Merdeka Curriculum requires psychological strength from teachers, including self-efficacy. The application of coaching after the Merdeka Curriculum training can increase teachers' self-efficacy. This study aims to prove that teachers' self-efficacy can be improved using coaching. This research is an experimental study with a sample of 34 early childhood education teachers from 59 'Aisyiyah Bustanul Athfal (ABA) kindergartens in Makassar City. The sample was selected based on certain criteria (purposive sampling). Data was collected using questionnaires. Data analysis used descriptive statistics. The results showed that there was a difference in the self-efficacy of early childhood education teachers after the treatment of learning based on the Merdeka Curriculum and the provision of coaching. There was an increase in self-efficacy scores before and after the provision of learning training using the Merdeka Curriculum. The increase in teachers' self-efficacy after receiving training and coaching indicates that coaching effectively prepares teachers to face changes in teaching practices, especially in implementing the Merdeka Curriculum.